2020
DOI: 10.1109/jiot.2019.2952721
|View full text |Cite
|
Sign up to set email alerts
|

Toward Optimal Resource Scheduling for Internet of Things Under Imperfect CSI

Abstract: The Internet of Things (IoT) increases the number of connected devices and supports ever-growing complexity of applications. Owing to the constrained physical size, the IoT devices can significantly enhance computation capacity by offloading computation-intensive tasks to the resource-rich edge servers deployed at the base station (BS) via wireless networks. However, how to achieve optimal resource scheduling remains a challenge due to stochastic task arrivals, time-varying wireless channels and imperfect esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Besides transceiver hardware impairments, channel estimation errors do exist in the system while estimating the channel state information (CSI) with the help of pilot symbols prior to the data symbols transmission. The impact of imperfect CSI is widely investigated in the IoT networks (see other works [36][37][38][39] and the references therein). Specifically, Jiao et al 36 have proposed an optimal resource scheduling algorithm under imperfect CSI in an IoT environment.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides transceiver hardware impairments, channel estimation errors do exist in the system while estimating the channel state information (CSI) with the help of pilot symbols prior to the data symbols transmission. The impact of imperfect CSI is widely investigated in the IoT networks (see other works [36][37][38][39] and the references therein). Specifically, Jiao et al 36 have proposed an optimal resource scheduling algorithm under imperfect CSI in an IoT environment.…”
Section: Related Workmentioning
confidence: 99%
“…The impact of imperfect CSI is widely investigated in the IoT networks (see other works [36][37][38][39] and the references therein). Specifically, Jiao et al 36 have proposed an optimal resource scheduling algorithm under imperfect CSI in an IoT environment. Ansere et al 37 have investigated joint optimization of user selection, power allocation, and the number of activated base station antennas of multiple IoT devices under imperfect CSI in order to maximize energy-efficiency.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Alli and Alam [33] surveyed the fog-edge computing for solutions proposed in studies involving IoT-fog-cloud ecosystems and predicted future growth patterns and raised open issues of the fog cloud of things and concluded that fogging offers a forum for providing services between resource-constrained and latency-sensitive connected devices. Jiao et al [34] analyzed the resource scheduling to optimize the time-averaged network performance for uplink IoT systems based on OFDMA. An optimization problem has been solved by using the Lyapunov optimization theory and the Lagrangian technique of dual decomposition.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[6]. Other applications include smart doorbells, smart transportation, smart restaurants, smart health devices, smart farms in agriculture, smart learning tools, pills enabled digestive sensors, smart medical bottles and smart clothes [7][8][9][10][11][12][13][14][15][16][17][18]. US National Intelligence Council has recommended IoT as one of the six 'disruptive civil technologies'.…”
Section: Introductionmentioning
confidence: 99%